Cost-effectiveness of nivolumab in the treatment of head and neck cancer. (December 2018) - Hirschmann, A.; Lupatsch, J.E.; Schwenkglenks, M.; Panje, C.M.; Matter-Walstra, K.; Espeli, V.; Dedes, K.J.; Siano, M.; ,
Highlights: Cost-effectiveness of nivolumab for HNSCC including follow-up data was assessed. From the Swiss health care perspective the ICER was 102, 957CHF per QALY. Follow-up data is essential for modelling for more precise estimations of the ICER. Abstract: Background: Until recently, no second-line treatment for recurrent and/or metastatic head and neck squamous cell cancer (r/mHNSCC) was able to improve overall survival (OS). Nivolumab has become a promising treatment for r/mHNSCC. The CheckMate-141 trial showed that nivolumab improves OS compared to investigator's choice (IC) (cetuximab, methotrexate, docetaxel). Treatment with immune checkpoint inhibitors is however expensive. The aim of this analysis was to assess the cost-effectiveness of nivolumab as second-line treatment for r/mHNSCC in Switzerland. Methods: Based on the CheckMate-141 trial, we constructed a Markov model comparing nivolumab to IC, including follow-up data up to 24 months. We assessed costs for treatments from the perspective of the Swiss health system with a 60 months' time horizon. PD-L1 and p16 testing were considered in scenarios. Incremental cost-effectiveness ratios (ICER) were compared to an informal willingness-to-pay of CHF (Swiss Francs) 100, 000 per QALY gained. Results: For the base case we estimated an incremental effectiveness of 0.35 QALYs and incremental costs of CHF 35, 562 with nivolumab, resulting in an ICER of CHF 102, 957 per QALY gained. Most influential drivers for the ICER were the price of nivolumab and the progressive disease state utility weights. In 45.5% of probabilistic sensitivity analysis simulations nivolumab was estimated below 100, 000 CHF/QALY. Reducing the price of nivolumab according to a consented payback by 4.75%, resulted in an ICER of CHF 98, 325/QALY gained. Conclusions: At current prices nivolumab has an ICER of around CHF 100, 000 per QALY gained in the second line treatment of r/mHNSCC patients in Switzerland.